The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsomega.0c04999
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Coatings Via Atmospheric-Pressure Plasma-Enhanced Chemical Vapor Deposition for Enhancing the UV-Resistant Properties of Transparent Plastics

Abstract: Herein, TiO 2 coatings were deposited on photodegradable polymers for protection from UV irradiation using the atmospheric-pressure plasma-enhanced chemical vapor deposition (AP-PECVD) technique. Polymethylmethacrylate (PMMA) and polycarbonate (PC) substrates were coated with titanium tetraisopropoxide as the precursor in an open-air atmosphericpressure nonequilibrium argon plasma jet. The AP-PECVDderived TiO 2 coatings exhibited good adhesion to PMMA and PC. The TiO 2 coatings could shield more than 99% of UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…Atmospheric-pressure plasma-enhanced chemical vapor deposition (AP-PECVD) enables high deposition rates, easy compositional control, high step coverage, minimal residue generation, and the possibility to form crystalline oxide semiconductor thin films at reduced temperature, thanks to the reactivity of plasma. In addition, operating under atmospheric-pressure conditions allows for the injection of precursors as aerosols, vastly extending the range of suitable precursors because of relying more on their solubility rather than volatility . Yet, literature reports on the AP-PECVD of oxide thin films for the photocatalytic and photoelectrochemical application mainly focus on simple oxides, such as TiO 2, ZnO, and SiO 2 . Therefore, the present study investigates the AP-PECVD of binary metal oxide thin films for solar energy harvesting. In particular, we report the atmospheric-pressure production of crystalline SrTiO 3 thin films on large-area substrates from the AP-PECVD reaction of halogen-free precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric-pressure plasma-enhanced chemical vapor deposition (AP-PECVD) enables high deposition rates, easy compositional control, high step coverage, minimal residue generation, and the possibility to form crystalline oxide semiconductor thin films at reduced temperature, thanks to the reactivity of plasma. In addition, operating under atmospheric-pressure conditions allows for the injection of precursors as aerosols, vastly extending the range of suitable precursors because of relying more on their solubility rather than volatility . Yet, literature reports on the AP-PECVD of oxide thin films for the photocatalytic and photoelectrochemical application mainly focus on simple oxides, such as TiO 2, ZnO, and SiO 2 . Therefore, the present study investigates the AP-PECVD of binary metal oxide thin films for solar energy harvesting. In particular, we report the atmospheric-pressure production of crystalline SrTiO 3 thin films on large-area substrates from the AP-PECVD reaction of halogen-free precursors.…”
Section: Introductionmentioning
confidence: 99%
“…The electron–hole pair state of the TiO 2 sites has been proved to be highly reactive; thus, due to the recombination of these pairs, and photogenerated charge carriers, the quantum efficiency of this material is relatively high 32 , 33 . Xu et al 21 investigated the transparency of PC/PMMA coated with TiO 2 film with granular morphology. It was observed that adding TiO 2 film could significantly enhance the stability against UV radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Titanium oxide (TiO 2 ) is considered as a practical nanoparticle in surface protection applications since it has a wide energy band gap of 3 eV , showing a strong UV light cutoff. Previously conducted works proved that thin films including TiO 2 could effectively protect UV-degradable materials, especially PMMA 21 , 22 . Harb et al 23 successfully synthesized homogeneous PMMA-TiO 2 and PMMA-ZrO 2 nanocomposites and studied their protective properties.…”
Section: Introductionmentioning
confidence: 99%
“…The gasification capacity and reducibility of the composite are increased. Xu et al [84] used CVD method to coat TiO 2 film on the polymer of polymethyl methacrylate and polycarbonate. The degradation rate constants of PMMA and PC decreased from 0.36 h À 1 to 0.018 h À 1 and from 0.23 h À 1 to 0.029 h À 1 , respectively, under single UV irradiation for 5 h. It indicates that the TiO 2 coatings prepared by this method can prevent the polymer degradation of PMMA and PC and improve their stability under UV irradiation.…”
Section: Chemical Vapor Deposition Methodsmentioning
confidence: 99%
“…The gasification capacity and reducibility of the composite are increased. Xu et al [84] . used CVD method to coat TiO 2 film on the polymer of polymethyl methacrylate and polycarbonate.…”
Section: Synthesis Of Nano‐tio2mentioning
confidence: 99%